A probing radar designed for simulation of radar echo of a meteorite within the ice sheet of the Antarctic Continent (I) (abstract) - Hoshiyama, Mitsuo; Nishitsuji, Akira; Nishio, Fumihiko; Wada, Makoto; Watanabe, Okitsugu (1986)
P(論文) departmental bulletin paper